(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Madhusudan wrote the first sonnets in Bengali and perhaps his sonnets are still considered to be the best sonnets written in Bengali. His Chaturdaspadi Kavitavali was published in Granthkara in 1866. The book contains more than 100 sonnets and the sonnets describe different subjects. The sonnets are filled with strange and multifarious themes as the memory of Madhusudan’s lost days unfolds. There are rivers, villages, Ramayana, Mahabharata, Kalidasa, Kavikankan, Bharatachandra, Vidyasagar through which the identity of his native soul can be found. Several of his sonnets have references to Ramayana, such as Kirtivas, Sita Devi, Sita - Banvase, Valmiki etc. Notable among his sonnets in which the context of Mahabharata appears are Kashiramdas, Mahabharata, Subhadraharan, Gogriha-rane, Gada Yudha, Subhadra, Urvashi etc. Besides, Mukundaram Chakraborty’s Chandimangal poetry is influenced in his Kamale Kamini, Srimant’s Topar sonnets and Bharatchandra’s Annadamangal poetry is influenced in Annapurna’s Jhampi and Ishwari Patni sonnets. Shaktpadavali is influenced by his Vijaya Dasami and Ashwin mas sonnets. As Madhusudan has portrayed mythological stories and characters through these sonnets, we can easily understand the special pull of his heart towards mythological stories by reading his sonnets.